Two 20th-century psychologists: Viktor E. Frankl and Hans Jürgen Eysenck, two decades after their deaths. - León Fernández, Ramón (2017)
Twenty years ago Viktor E. Frankl and Hans Jürgen Eysenck passed away. In the present communication the author discusses the significance of their works and ideas to psychology. Frankl was the founder of logotherapy, an important psychotherapy theory which at the present enjoys of worldwide attention, Eysenck put the basis for the behavioral therapy and was a very important researcher in the the psychology of personality.